Indigenous enlightenment: printing and education in evangelical colonialism, 1790-1850 - McKee, Stuart D. (University of Nebraska Press, 2023)
In Indigenous Enlightenment Stuart D. McKee examines the methodologies, tools, and processes that British and American educators developed to inculcate Indigenous cultures of reading and learning between 1790 and 1850